Investigating the potential of using moringa oleifera husks for bioethanol production - Nurul Mimi Suziana , Abdul Aziz (2013)
This study is mainly focusing on ethanol production from Moringa oleifera husks, which is an agricultural waste with no appreciable value to industries or competitive use as food. Such waste presents high concentration of carbohydrates, thus it can be viewed as a potential raw material for bio ethanol production. It was good to introduce to others the advantages or uses of husks instead of being thrown away or burnt and to prove zero waste from this plant. Hence, the objective of this research was to evaluate the feasibility of ethanol production by fermentation of Moringa oleifera husks by Saccharomyces cerevisiae. Batch fermentation studies were performed with different yeast concentration. The methods used included acid hydrolysis with 5% H2SO4, followed by the fermentation with Saccharomyces cerevisae. Yeast concentration was evaluated at 1, 3 and 5 g/L and fermentation temperature was kept constant at 300C. After that, a simple fractional distillation was done to get the final product from the fermented broth. The yield of ethanol was analysed by using gas chromatography analyzer in terms of ethanol concentration (g/L). Ethanol yield from Moringa oleifera husks was maximum at 12th hour with ethanol concentration of 4.9747 g/L. This maximum yield was from the fermented broth with yeast concentration of 1 g/L. It was observed that fermentation yield decreased with an increase in yeast concentration and fermentation time. However, the results indicated that the agricultural waste such as Moringa oleifera husks could be considered as a potential lignocellulosic material for production of fermentable sugars related to bio ethanol production